Axial behavior of novel CFDST columns with outer welded corrugated steel tubes. (December 2021) - Su, Rong; Li, Xian; Zhong, Tao; Zhou, Tao
Abstract: A novel type of welded corrugated steel tube-concrete-flat steel tube composite structural column was proposed, and the axial compressive behavior of this column type was evaluated by testing of 14 short column specimens. The test parameters included hollow ratios, inner tube diameter-thickness ratios, and concrete strength and reinforcement ratios. The test results indicated that the outer corrugated steel tube could provide good hoop confinement to the core concrete. The welded corrugated steel tube-concrete-flat steel tube composite structural columns failed with serious extrusion of the wave crests and inward buckling of the inner steel tubes. The effects of the test parameters on the failure modes, strength, and ductility and strain responses were also discussed. Moreover, some existing design models for concrete-filled double skin tubular (CFDST) columns were assessed based on the test results available in literature and this study, and new models for CFDST columns and welded corrugated steel tube-concrete-flat steel tube columns were proposed. The proposed analytical models were found to be in good agreement with both the test results of the specimens with outer flat steel tubes and corrugated steel tubes under axial compression.